TRANSMISSION COEFFICIENT OF POWER DENSITY INTO SKIN TISSUE BETWEEN 6 AND 300 GHZ. Issue 1 (4th December 2020) - Christ, Andreas; Samaras, Theodoros; Neufeld, Esra; Kuster, Niels
Abstract: The latest electromagnetic safety guidelines define transmitted or epithelial power density as the basic restriction above 6 GHz. In this note, we derive an approximation for a conservative transmission coefficient for quasi plane wave incidence as a function of the frequency for the normal component of the Poynting vector with respect to the evaluation plane or tissue surface | S z inc | and for its modulus ||Sinc ||. The maximum transmission coefficient for the normal component of the Poynting vector ${\boldsymbol{T}}_{z}^{max}$ is 1 independent of tissue composition and frequency. Approximations of ${\boldsymbol{T}}_{total}^{max}$ normalized to ||Sinc || for thin and thick stratum corneum are provided allowing higher exposures. These approximations allow to conservatively demonstrate compliance with basic restrictions when quasi plane-wave conditions are locally satisfied and enhancement effects of standing waves between source and body can be neglected. The reported results are important to regulators and standardization bodies regarding revisions of compliance requirements and safety guidelines.